Teacher training for early childhood education and first years - senses, meanings and diversity of knowledge and practices in the context of deaf education (Olhar de Professor, 2024)
This article discusses the relationship between the pedagogues training and the construction of senses, meanings, and diversity of knowledge of practices in the context of deaf education in Early Childhood Education and the initial years of Elementary School. The research presented here articulated issues related to the initial training, knowledge and skills of the pedagogue teacher and the production of teaching materials in the teaching and learning process of deaf people, in a Pedagogy course, in the year 2023. The research carried out is framed in the case study modality, with a qualitative-interpretative bias and used Discursive Textual Analysis in the discussion of the data. The main results point to a reflection on the deaf person as a subject who communicates and expresses himself through sign language, which makes it necessary to overcome hearing-based pedagogical practices.
Keywords: Teacher training; Early childhood education and first years; Education of the deaf